A Hybrid Passive Cooling Wall System: Concept and Laboratory Testing Results. (November 2015) - Grosso, Mario; Fracastoro, Gianvincenzo; Simonetti, Marco; Chiesa, Giacomo
Abstract: The research unit associated to the Laboratory Systems for Technology Innovation (LaSTIn) of the Department of Architecture and Design as well as the Department of Energy, Polytechnic University of Turin, has investigated the possibility of producing a modular wall system for hybrid/natural passive cooling. This system uses pressure differences typical of natural air movements and it is conceived as a mean to reach a quasi-zero-energy building as foreseen by Dir. 2010/31/EU by 2020 for new constructions. In addition, it realises a high level of technological and architectural integration in building constructions. The research focuses on passive and solar cooling techniques and studies the following possible systems, designed and tested separately in laboratory: a) latent heat adsorption cells including silica gel and zeolites for controlling the specific air humidity content, with heat regeneration by a vacuum water solar collectors system; b) a low-pressure heat exchanger, with crossing flows through ducts of rectangular section, to recover sensible heat/cold from return air; c) a passive evaporative cooling element. This paper present the design concept of the wall system as well as a first series of results from laboratory testing regarding the latent heat absorption component.